Stimulating the Banking Sector Participation in the System of the Real Sector of Economy Support - E. V. Altukhova; M. A. Markov (Вестник Российского экономического университета имени Г. В. Плеханова, 2020)
The development of the real sector is essential to ensure the growth of national economy in any country. The principle institution working with money in economy is banks. They maintain cash circulation of real sector companies and act as a source of investment, which is allocated in the form of banking credits. Taking into account the fact that the goal of stimulating the real economy growth is set not only for the banking system but for economy in general, the approach to its attaining should be complex and systematic. Because of that it is very important to develop a list of steps that could provide a differentiated approach in the system of supporting companies of the real sector. Such measures’ implementation includes the participation of development institutions and therefore, banks in the system of national projects realization. Upgrading legislative regulation in the sphere of interaction between banks and business entities is extremely important as well as the development of new finance tools providing the growth in finance potential in the real sector of economy. The article analyzes banks’ participation in crediting the real sector of economy in Russia, studies the key characteristics of crediting and puts forward steps both on the macro- and micro-level, which could coordinate economic interests of companies and banks and cut costs.